Socioeconomic characteristics and life skills of medical students: A cross-sectional study - Dadgarmoghaddam, Malihe; AkhavanRezayat, Arash; Omranzade, Alireza; Shiehzadeh, Elham; Saghebi, Ali; Niroumand, Shabnam (Social Determinants of Health, 2019)
Background: The current medicine teaching curriculum has caused medical students several psychological ailments including depression, and stress. Our study aimed to find a relationship between some socioeconomic characteristics of medical student and their life skills at Mashhad University of Medical Sciences, Iran. Methods: 146 Interns of Mashhad University of Medical Sciences were enrolled in our cross-sectional study by census. The framework was obtained from education department of faculty. Students reported a history of psychological disorders, and foreign students were excluded. We evaluated participant’s Proficiency in computer, habitat, parent’s education, and family income and life skills. Data were analyzed by SPSS Inc. Released 2007. SPSS Inc. Released 2007. SPSS for Windows, Version 16.0. Results: Participants aged between 22 to 27 and 98 (66.2%) of them were female. Comparison between four levels of father’s education (lower than diploma, diploma, bachelor and higher than bachelor) showed worldview (P=0.014), social behavior (P=0.011) and ability to use new technologies (P=0.018) had a significant difference. Regarding the mother’s education, there are no significant differences among 20 life skills. There were significant differences between levels of computer proficiency and communication skills (P=0.042), interpersonal relations (P=0.011), mental health status (P=0.035), problem-solving (P=0.021), creativity (P=0.013), ability of using new technologies (P=0.001), participate in activities that improve benefits (P=0.027), and total score (P=0.043). Conclusion: Despite mothers’ education, fathers’ education has a role in medical students’ world view, technology access, and social behavior. However, comparison of means and subgroup analysis didn’t show a logical relationship. Computer proficiency besides affecting different aspects of life skills can affect total life skill scores.